EMPLOYEES INTELLECTION INVESTIGATIONTOWARDS METROPOLITAN TRANSPORT CORPORATION (CHENNAI) LTD - Vilvijaya, Dr. C. (International Journal of Psychosocial Rehabilitation, 2017)
To seek satisfaction by an individual in general but it is complex to measure accurately the level of job satisfaction perceived by employee particularly in Employees Intellection Investigation Towards Metropolitan Transport Corporation (Chennai) Ltd whenever a research study the working environment and work culture. The various dimension of working environment such the corporation policies, service system, inter - personal relationship, supervision, working hours, recognition of employees, responsibilities, work tasks are the major factors to judge the job satisfaction. It is important for every corporation to care about the employees’ IntellectionInvestigation through these factors.